DEVELOPMENT AND PRESERVATION OF NATIONAL CULTURE SOCIAL FACTORS (Scientific journal of the Fergana State University, 2026)
In this article, national culture primarily defines the identity and uniqueness of a people. Through language, customs, rituals, and folklore, a nation distinguishes itself from other nations. One of the most important factors in the process of developing and preserving national culture is identification, that is, self-awareness. Because culture is not only a collection of material and spiritual heritage, but also expresses people's conscious attitude towards their nation, values, and historical roots. Identification refers to the process of connecting a person with a particular nation, society, or culture. Through this process, it is highlighted that a person is closely connected with their historical roots, traditions, customs, language, and religion.